Development and Validation of a simple score for diagnosis of Leptospirosis at outpatient departments - Temeiam, Nidhikul; Jareinpituk, Sutthi; Phinyo, Phichayut; Patumanond, Jayanton; Srisawat, Nattachai (PLOS Neglected Tropical Diseases, 2020)
Author summary Leptospirosis is an important tropical infectious disease. Early diagnosis of leptospirosis in patients with mild and vague clinical syndrome is another clinical obstacle. Most of the diagnostic score developed for diagnosis of leptospirosis are based on patients with flank clinical symptoms, mostly in hospitalized patient. This study developed the OPD score for early diagnosis of undifferentiated fever for patients visiting outpatient care in leptospirosis endemic area. This score can be practically apply to area where health care facilities are limited by asking patients for only two potential risk factors of exposure to Leptospira, taking simple blood and urine samples. We believed that this score could aid physician in early diagnosis and initiation of treatment in early leptospirosis patient which would alleviate disease progression and probably decrease mortality.